ANALYSIS OF THE ACTIVITIES OF EDO STATE AGRICULTURAL DEVELOPMENT PROGRAM EXTENSION SERVICES AMONG SMALL-SCALE CASSAVA FARMERS - Ehilenboadiaye, C. O.; Onemolease, E. A.; Omoregie, O. (FUDMA Journal of Sciences, 2021)
This study assessed the expectations of cassava tuber farmers from the agricultural extension service providers in Edo State, Nigeria. It examined the support presently given to cassava farmers by the extension service viz-a-viz the needs of the farmers. To achieve these objectives, data were collected from 196 cassava tuber producers, randomly sampled from the three agricultural zones in the State. Data were analysed using descriptive and inferential (multiple regression, Friedman and Cochran tests) statistics. Cochran test (Ï‡2 = 596.35; p
Keywords: Cassava, extension needs, role, support, agricultural development programme